Lateral and axial displacements measurement using fiber optic sensor based on beam-through technique - Yasin, Moh; Harun, Sulaiman Wadi; Fawzi, W.A.; Kusminarto, -; Karyono, -; Ahmad, Harith (John Wiley & Sons, 2009)
The performance of the fiber-optic displacement sensor with beam-through detection technique is investigated. The effects of lateral and axial displacements on the detected output voltage are investigated for various core's diameters of the sensor. The highest sensitivity is obtained at 0.0008 mV/μm for the lateral displacement with core's diameters for both transmitting and receiving fibers are fixed at 0.5 mm. At present, the widest linear range is obtained at 3195 μm for the axial displacement with 1.0 mm core's diameters for both fibers. The highest resolution of the 13 μm is obtained with the lateral displacement sensor with 0.5 mm core diameter. The sensor with the smaller core shows a better sensitivity and resolution with the expense of the smaller linear range. The beam-through sensors have a simple design, high degree of sensitivity and dynamic range, and low cost. These make the sensors are useful for microdisplacement measurement in the hazardous region.